STUDI DESKRIPTIF KUANTITATIF: TINGKAT RELIGIUSITAS PADA DEWASA AWAL YANG MENGALAMI ADVERSE CHILDHOOD EXPERIENCES DI KOTA KUPANG - Sandra Paula Blansiska Bria; Diana Aipipidely; Rizky Pradita Manafe; Mariana Ch Lerik (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Early adulthood is a crucial transitional phase faced with heavy developmental demands, where an individual's psychological well-being is often threatened by the long-term impact of past trauma in the form of Adverse Childhood Experiences (ACE). The focus of this research problem is to describe in depth the level of religiosity in early adults in Kupang City who have a history of adverse childhood experiences. The research steps were carried out through a quantitative descriptive approach involving 383 respondents aged 18 to 25 years as the research sample. Data were collected using the ACE Scale which covers 13 types of traumatic experiences and The Centrality of Religiosity Scale which measures five main dimensions of spirituality, then the data were analyzed using descriptive statistics. The quantitative research findings revealed that the majority of participants, namely 73.1%, were in the high to very high ACE category, while their religiosity profile also showed a very significant percentage in the high to very high category at 91.9%. The main conclusion of this study confirms that high exposure to adverse childhood experiences does not automatically reduce an individual's spiritual commitment. In the socio-cultural characteristics of the religious city of Kupang, religion remains a prominent identity and a source of coping for young adults to make sense of life despite their difficult past history, which also becomes an important basis for designing spirituality-based psychological interventions in the future.